Does Giving and Receiving Helping Behavior Fit Matter? The Role of Neighboring Behavior Fit in Working Residents' Mental Health - Xiu, Jing; Zhang, Zhenduo; Fan, Youqing; Zheng, Junwei (Frontiers in Public Health, 2022)
Ecological systems theory suggests that for individuals, the three domains of community, family, and work are connected and transfer resources among each other. In the community, residents receive and give helping behavior from and to their neighbors. Neighboring behavior underlies interactions among residents in the community, thereby influencing the work and family domains. Building on ecological systems theory, the authors propose that the compatibility of receiving and giving helping behavior among working residents is related to their mental health. Additionally, the authors propose that this congruence effect functions through work-family interference and meaning in life. Using a two-stage field questionnaire survey, this study collected data from 220 full-time Chinese working residents. Using polynomial regression and response surface analysis, receiving-giving neighboring behavior fit was found to be positively associated with mental health. Furthermore, receiving-giving neighboring behavior fit enhances mental health by decreasing work-family interference and promoting meaning in life. When giving and receiving neighboring behavior are imbalanced, working residents have higher levels of mental health when they received more neighboring behavior than they gave, in comparison to the condition when they gave more neighboring behavior than they received. Work-family interference represents inter-role conflict in which pressures from the family and work domains are mutually incompatible. Including both work to family interference and family to work interference, work-family interferences reflect the stress that working residents experience in their family and work domains. By exploring the mediating role of work-family interference, this study shows how the spillover of the benefits of neighboring behavior into the family and work domains enhances working residents' mental health. This study highlights the importance of balancing receiving and giving neighboring behavior for maintaining mental health, thus contributing both theoretically and practically to ecological systems theory.